Novel glucoamylase-resistant gluco-oligosaccharides with adjacent α-1, 6 branches at the non-reducing end discovered in Japanese rice wine, sake. (1st January 2021) - Honda, Chihiro; Katsuta, Ryo; Yamada, Mariko; Kojima, Yusuke; Mamiya, Ayane; Okada, Nanako; Kawamura, Takuya; Totsuka, Akira; Shindo, Hitoshi; Hosaka, Masaru; Nukada, Tomoo; Tokuoka, Masafumi
Highlights: Oligosaccharides in sake consist of isomers with different branching patterns. Novel gluco-oligosaccharides, DP6-1, DP7-1, DP8-1, and DP8-2 were isolated from sake. Unique adjacent α-1, 6-branches are present at the non-reducing ends of DP6-1. DP6-1 is resistant to glucoamylase digestion probably due to the adjacent branches. Low digestibility accounts for DP6-1 as residual saccharides in sake. Abstract: Sake, a traditional Japanese rice wine, contains various oligosaccharides (Sake oligosaccharides; SAOs) derived from rice starch. We previously found that SAOs reach a high degree of polymerization (DP). In this study, we developed a hydrophilic interaction liquid chromatography-time-of-flight/mass spectrometry (HILIC-TOF/MS) based analytical method to separate isomeric SAOs. Isomers of SAOs with DP = 6, 7, and 8, which were named DP6-1, DP7-1, DP8-1 and DP8-2, respectively, were purified from sake and their structures were determined by two-dimensional NMR spectroscopy. These were novel oligosaccharides containing two α-1, 6 bonded branches on an α-1, 4-linked glucose main chain. Interestingly, adjacent double α-1, 6 branches that have not been identified in starch, were found in DP6-1, DP7-1, and DP8-1, suggesting the presence of the branching pattern in starch. DP6-1 was poorly digested by fungal glucoamylase, and this may be attributed to its adjacent double branches at the non-reducing end.